Application of ULDF to determine maximum drop size produced by pneumatic atomiser / Fauziah Jerai@Junaidi and Ow Chee Sheng (Faculty of Mechanical Engineering and University Publication Centre (UPENA), 2007)
Pneumatic atomisers are well suited to the production of sprays with average drop diameter less than 30fim mass mean diameter depending on the pressure used. The maximum size of the drops formed are a function of the design of the atomiser. In this study, droplet size in a pneumatic atomiser was measured using a laser diffraction technique. The conversion of number count to volume distribution is computed using the Integral Method instead of using the data provided by the measuring device. In addition, the maximum droplet size, X is determined graphically by fitting the data into the Upper Limit Distribution Function, ULDF. Optimisation of fit with ULDF also provided Sauter Mean Diameter, X₃₂ and Volume Mean Diameter, X₃₀ which compare well with the Integral Method of sizing. As a result of this work, drop sizes in pneumatic atomiser can be estimated with great accuracy.